1999
DOI: 10.1021/ma9912406
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructure Formation via Association of Tectons in Amorphous Polymer Matrices

Abstract: The supramolecular assembling of small amounts of octyl- and benzyl-substituted complementary tectons based upon barbiturates (BA) and 2,4,6-triaminopyrimidines (TP) was studied in a polystyrene matrix by means of differential scanning calorimetry (DSC), dynamic-mechanical spectroscopy, and transmission electron microscopy (TEM). Self-organization of these tectons within the compounds drastically changes the melt rheology in comparison to the pure matrix. Depending on external conditions such as temperature an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 21 publications
1
31
0
Order By: Relevance
“…Previous studies have shown that micro-and nanosized pores can be formed by VIPS in thin films. 64,65 This principle was applied to produce the BNTHP membranes in our study. Various process parameters (i.e., solvent volatility, initial polymer concentration, and relative humidity, etc.)…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Previous studies have shown that micro-and nanosized pores can be formed by VIPS in thin films. 64,65 This principle was applied to produce the BNTHP membranes in our study. Various process parameters (i.e., solvent volatility, initial polymer concentration, and relative humidity, etc.)…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This behavior is similar to what we already observed for PS compounds. 9 The only difference is the absolute value of the transition temperature: The formation and dissolution temperatures of the assemblies are significantly lower in PS compared with PP.…”
Section: Resultsmentioning
confidence: 99%
“…From the literature 8,9 we know that equimolar mixtures of OT crystallize and melt at temperatures around 170 and 190 °C, respectively. These characteristic transition temperatures and the morphology of the samples are strongly influenced by the presence of a solvent (here polymer; for details see Guenet 16 and Terech and Weiss 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, “supramolecular polymers” display unique rheological properties due to the reversibility of the hydrogen-bonding interactions between mesogenic or polymeric components . Small molecule additives with hydrogen bonding groups, such as 1,3:2,4-dibenzylidenesorbitol or various substituted binary complexes of barbiturates and 2,4,6-triaminopyrimidines, spontaneously form three-dimensional continuous fibrillar networks in host polymers. These networks, in both the melt and crystalline state, can produce measurable effects on the mechanical properties of the blends at low concentrations of the small molecule component (<3%).…”
Section: Introductionmentioning
confidence: 99%